Primary hyperaldosteronism associated to an adrenal neoplasia. Case report - Bravo-Zúñiga, Jessica (2023)
We report the case of a 68-year-old male with a history of non-treated arterial hypertension diagnosed the previous year that was admitted with anasarca, muscle weakness and dyspnea at rest. The first laboratory exams showed severe hypopotassemia, metabolic alkalosis, renal and gallbladder lithiasis and chronic renal disease. The abdominal tomography revealed a right suprarenal tumor, bilateral hydronephrosis and renal and gallbladder lithiasis. Under the suspicion of primary hyperaldosteronism, the diagnosis was confirmed with the determination of the relationship between aldosterone/direct renin concentration, which was high. The metabolic study showed hypercalciuria and hyperuricosuria and the potassium trans tubular gradient was above 7. The patient underwent right nephrectomy, nonetheless, died at the immediate post-operatory period due to a hypovolemic shock and respiratory failure.